Experimental media policy. (1st September 2016) - Herzog, Christian; Beck, Hanno
Experiments are part of the methodological toolkit in empirical political, economic and social science research. However, perhaps surprisingly, there is very little elaboration on the use and potential of experiments for media and communications policy, an issue addressed in this article. To float the idea we introduce some basic features of experiments and experimental approaches. Subsequently, five models of broadcasting organization that differ in their level of market proximity are introduced. Building upon these models, the article develops one suggestion for a quasi-experiment that starts from the hypothesis that the attitude towards PSM organizations can be positively changed when licence-fee contributors have ex ante control over certain programme-making decisions. The experiment would involve allocating a small proportion of licence-fee funds, over a predetermined period, to a newly designed participatory and transparent programme-making scheme. Eventually it could test whether such policy measures are deemed right to positively affect individual attitudes towards PSM organizations. Finally, the article calls for the more systematic inclusion of experimental research designs into media policy scholarship, making a case for experimental media policy as a sub-discipline in its own right.